1993
DOI: 10.1007/bf01316495
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of scintigraphy with indium-111 leukocyte scan and ultrasonography in assessment of x-ray-demonstrated lesions of crohn's disease

Abstract: The aim of this study was to compare the results obtained with an indium-111 scan with those obtained with less expensive and harmless ultrasonography to evaluate the location and inflammatory activity of Crohn's disease. Thirty-one patients previously studied with x-ray underwent abdominal 111In scans and ultrasonography (US). Sensitivity and specificity of US in detecting lesions seen with 111In scan were 77% and 92.8%, respectively. Sensitivity and specificity of 111In scan in detecting x-ray-defined lesion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(18 citation statements)
references
References 14 publications
1
17
0
Order By: Relevance
“…Numerous studies have demonstrated that increased leukocyte accumulation in active IBD correlates well with disease extent and severity in CD, compared with endoscopy, histology, and fecal excretion of 111 In-leukocytes (10)(11)(12)(13)(14)(15)(16)(17)(18)(19). For inpatients with symptoms of small bowel obstruction (a population somewhat similar to ours, though probably with more severe active disease because 76% of our patients were outpatients) and positive enteroclysis, a negative 111 In-leukocyte scan was reported to be suggestive of chronic fibrostenotic stricture, not acute inflammatory disease, due to lack of response to medical therapy (18).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous studies have demonstrated that increased leukocyte accumulation in active IBD correlates well with disease extent and severity in CD, compared with endoscopy, histology, and fecal excretion of 111 In-leukocytes (10)(11)(12)(13)(14)(15)(16)(17)(18)(19). For inpatients with symptoms of small bowel obstruction (a population somewhat similar to ours, though probably with more severe active disease because 76% of our patients were outpatients) and positive enteroclysis, a negative 111 In-leukocyte scan was reported to be suggestive of chronic fibrostenotic stricture, not acute inflammatory disease, due to lack of response to medical therapy (18).…”
Section: Discussionmentioning
confidence: 99%
“…Noninvasive anatomic and functional imaging modalities, including CT enteroclysis (6)(7)(8)(9), CT enterography, ultrasound, magnetic resonance enterography, and radiolabeled white blood cell and granulocyte scintigraphy (10)(11)(12)(13)(14)(15)(16)(17)(18)(19), have shown some ability to measure the extent and severity of active inflammation in CD. Neither these techniques nor endoscopy allows complete assessment of transmural inflammation or extraluminal complications of CD.…”
mentioning
confidence: 99%
“…9,14,19,22,46,49,52,57,58,61,62 Only 1 study was performed in a pediatric population. 52 Ten studies considered CDAI as reference standard.…”
Section: Assessment Of Disease Activitymentioning
confidence: 99%
“…[9][10][11][14][15][16][17][18][19]22 Only 1 study was performed in a pediatric population. 16 One systematic review was also considered.…”
Section: Assessment Of Disease Locationmentioning
confidence: 99%
“…18,22,28 Most of these studies agreed in reporting the highest sensitivity (approximately 90%) of US in detecting ileal lesions but less accuracy in detecting lesions located in the upper small bowel and rectum. The accuracy of detection of Crohn's disease lesions in the proximal small bowel can be significantly improved by the use of oral contrast agents, whereas the sensitivity in detecting ileal and colonic lesions is comparable between conventional and oral contrast US.…”
Section: Evaluation Of Site and Extension Of Crohn's Diseasementioning
confidence: 90%